2014
DOI: 10.2135/cropsci2013.09.0604
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate and Lipid Dynamics in Wheat Crown Tissue in Response to Mild Freeze–Thaw Treatments

Abstract: Freezing tolerance resulting from cold hardening is critical to survival of fall‐seeded winter wheat. Exposure of winter wheat plants to cycles of freeze–thaw at temperatures just below, and just above freezing results in incremental improvements of freezing tolerance. Changes in the concentrations of carbohydrates in the cellular fluids of wheat crowns, and of lipids extracted from wheat crown tissue, were quantified following exposure to 24 h freeze(s) at –3°C, with or without a following thaw of 24 h at 3°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…In this study, Pearson's correlation analysis showed that the accumulation of soluble sugar, starch, and protein were positively correlated with the changes in of fresh and dry weight of grain (Figure S1), which was consistent with previous studies (Zhang et al, 2021;Zhao et al, 2022). Changes of grain yield under LT stress were also affected by cellular carbohydrates, lipids, cell viability, and gene expression (Laudencia-Chingcuanco et al, 2011;Skinner et al, 2014). The decrease in the kernel weight of YN7 under the LT treatment was greater than that of SYN5, indicating that YN7 was more sensitive than SYN5.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, Pearson's correlation analysis showed that the accumulation of soluble sugar, starch, and protein were positively correlated with the changes in of fresh and dry weight of grain (Figure S1), which was consistent with previous studies (Zhang et al, 2021;Zhao et al, 2022). Changes of grain yield under LT stress were also affected by cellular carbohydrates, lipids, cell viability, and gene expression (Laudencia-Chingcuanco et al, 2011;Skinner et al, 2014). The decrease in the kernel weight of YN7 under the LT treatment was greater than that of SYN5, indicating that YN7 was more sensitive than SYN5.…”
Section: Discussionsupporting
confidence: 91%
“…The observed sequential increase, then decrease in freezing tolerance is consistent with our previous findings showing that exposing the plants to -3°C resulted in sequential, extensive reengineering of the transcriptome [ 16 ], and of cellular composition [ 33 ], accompanied by significant increases in freezing tolerance [ 41 ]. Others have shown that ice crystal formation begins at about -3°C in wheat tissues [ 42 ] suggesting that the variation in expression of freezing tolerance at the time points studied ( Fig 1 ) probably originated in this initial response to -3°C and ice crystal formation.…”
Section: Discussionsupporting
confidence: 90%
“…We previously found that ORFW is capable of responding to freezing stress in some ways similar to Norstar and Tiber. For example, lipid dynamics in response to six low-temperature treatments were very similar in ORFW and five other cultivars, including Norstar and Tiber [ 33 ], indicating that some components of the low-temperature response of the cold-sensitive ORFW function similarly to those components in more cold-tolerant genotypes. This observation suggests that different pathways may significantly contribute to freezing tolerance in the different genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicated that the freeze at −3°C activated processes that were amplified and diversified after the freeze stress was removed. We further showed that the −3/3°C freeze-thaw treatment resulted in extensive changes to cellular carbohydrates and lipids (Skinner et al 2014), indicating that the transcriptome changes are accompanied by structural changes at the cellular level. By understanding the extent into the growth cycle that the freeze-thaw enhancement of freezing tolerance may be effective, and by characterizing differences in the response among cultivars, it may be possible to develop plant lines that more effectively make use of this phenomenon.…”
Section: Introductionmentioning
confidence: 77%
“…Plants were grown at 4°C for 6-13 wk, the period of time during which the differences in survival following 2FTP compared with PF were statistically significant. lipid components of the cells (Skinner et al 2014). The result of this transcriptome and cellular component re-engineering appears to be a significant increase in the ability of the plants to withstand subsequent freezing to potentially damaging temperatures.…”
Section: Discussionmentioning
confidence: 99%